Cognitive and Behavioral Predictors of Light Therapy Use - Roecklein, Kathryn A. (Public Library of Science, 2012)
OBJECTIVE: Although light therapy is effective in the treatment of seasonal affective disorder (SAD) and other mood disorders, only 53–79% of individuals with SAD meet remission criteria after light therapy. Perhaps more importantly, only 12–41% of individuals with SAD continue to use the treatment even after a previous winter of successful treatment. METHOD: Participants completed surveys regarding (1) social, cognitive, and behavioral variables used to evaluate treatment adherence for other health-related issues, expectations and credibility of light therapy, (2) a depression symptoms scale, and (3) self-reported light therapy use. RESULTS: Individuals age 18 or older responded (n = 40), all reporting having been diagnosed with a mood disorder for which light therapy is indicated. Social support and self-efficacy scores were predictive of light therapy use (p's<.05). CONCLUSION: The findings suggest that testing social support and self-efficacy in a diagnosed patient population may identify factors related to the decision to use light therapy. Treatments that impact social support and self-efficacy may improve treatment response to light therapy in SAD.